Desempenho das respostas adotadas no combate à pandemia de COVID-19: um comparativo dos determinantes sociopolíticos e macroeconômicos da China e dos EUA - MORAES, Felipe Araujo de (2023)
The coronavirus pandemic represents one of the most unexpected and violent global shocks that has profoundly affected human life. Faced with the diversity of results observed in the responses carried out by each country, it is necessary to investigate which factors may have been decisive for the success of some and which factors explain the failure of others. In order to identify these determinants, this work makes use of two response experiences: China and the United States of America. The research carries out a comprehensive review of the recent literature on the pandemic and, from a qualitative approach, seeks to understand the proposed problem both from the sociopolitical and institutional perspective and from the macroeconomic aspect. Despite being the epicenter of the virus, China recorded data on cases and deaths from Covid 19 below that recorded by the US, and even the economic impacts of the crisis were softer in China than in the US. It stands out how the State's movement, as well as the pre-established sociopolitical and socioeconomic conditions, were fundamental to generate coordination and assertiveness in the response to the pandemic crisis. In this sense, it is not just a question of stimulating activity via economic policy, given that the magnitude of the expenditure was not decisive for the success of the responses or, even, of just preventing the virus from spreading, but concatenating the two with a suitable environment. That is, to guarantee a minimum initial control of the virus combined with a socio-political and institutional environment that favors collaboration between the different groups in society, finally allowing the recovery of economic activity and the mitigation of the crisis to be validated.